2002
DOI: 10.1002/1522-2683(200204)23:7/8<985::aid-elps985>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Electroelution without gel sectioning of proteins from sodium dodecyl sulfate-polyacrylamide gel electrophoresis: Fluorescent detection, recovery, isoelectric focusing and matrix assisted laser desorption/ionization-time of flight of the electroeluate

Abstract: A method of direct electroelution of intact proteins, without gel sectioning and orthogonal to the orientation of electrophoretic migration, was developed in application to Novex gels, using a simple home-made experimental setup. Six model proteins covering the molecular mass range of 14-120 kDa were subjected to sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), stained with an aqueous solution of the fluorescent dye, SYPRO-red, and electroeluted from the intact gel. The sensitivity of visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…To visualize all three peaks at once, multiple fluorescence images taken at different excitation wavelengths were merged into a single image electronically. The two peaks observed for the carbonic anhydrase II protein are charge isomers of the same protein, as observed previously [25].…”
Section: Resultssupporting
confidence: 85%
“…To visualize all three peaks at once, multiple fluorescence images taken at different excitation wavelengths were merged into a single image electronically. The two peaks observed for the carbonic anhydrase II protein are charge isomers of the same protein, as observed previously [25].…”
Section: Resultssupporting
confidence: 85%
“…SDS-PAGE, perhaps the most popular electrophoretic technique for rapid assessment of protein purity and M r values, also appears as a promising technique for microscale preparative runs. Disregarding past attempts at eluting protein zones via cutting out of stained zones, recent methodologies have focused on the possibility of direct electroelution of proteins from SDS-PAGE gels without gel sectioning. While such techniques could be applied to both 1D and 2D gels, a shotgun electroelution system, driving a multitude of proteins spots resolved in a 2D surface into a multichambered, gridlike layer composed of as many as 384 wells has been described, as a proteomic tool for large-scale analysis of resolved polypeptide chains at the end of a 2D mapping process …”
mentioning
confidence: 99%
“…20,21 Buzás 20 compared the protein recovery using this apparatus and in-gel digestion, and the results indicated that this apparatus produced a high recovery. Radko 21 studied various aspects of this application including visualized detection, eluted protein recovery, IEF of the electroeluate and MALDI-TOF-MS of SDS-proteins after elution and ultrafiltration. This electroelution apparatus is capable of fast elution but only permits the elution of a single band at a time.…”
Section: Introductionmentioning
confidence: 99%